Non-Native Decapods in South America: Risk Assessment and Potential Impacts - de Oliveira, Lucas Rieger; Brito, Gustavo [UNESP]; Gama, Mafalda; Ovando, Ximena María Constanza; Anastácio, Pedro; Cardoso, Simone Jaqueline (MDPI, 2023)
Biological invasions pose significant challenges in the Anthropocene, impacting ecosystem biodiversity and functioning. Ecological Niche Modeling is widely used to evaluate potential areas at risk of invasions, aiding in the prevention of invasive-species expansion and guiding conservation efforts in freshwater ecosystems. The main objectives of this study were to model the ecological niche and evaluate remaining suitable habitat areas for the occurrence of five potentially invasive species of freshwater decapods in South America: Dilocarcinus pagei, Macrobrachium amazonicum, M. jelskii, M. rosenbergii, and Procambarus clarkii. Occurrence data from the Global Biodiversity Information Facility were complemented with a literature systematic review. Variables used in the models were obtained from the Worldclim and EarthEv databases. Ecological Niche Modeling was performed using the Biomod2 and sdm package algorithms. Our results indicated a suitable area of up to 11% of South America. Model evaluations yielded favorable TSS and AUC values (>0.7 and >0.8). The suitable areas projected for South America included several hydrographic basins and Protected Areas. The information generated in our study can help identifying areas susceptible to decapod invasion in South America and support local management and decisions.
Keywords: biological invasions; crustaceans; niche modelling